2015
DOI: 10.1080/10256016.2015.1011634
|View full text |Cite
|
Sign up to set email alerts
|

Release of nitrous oxide and dinitrogen from a transition bog under drained and rewetted conditions due to denitrification: results from a [15N]nitrate–bromide double-tracer study

Abstract: Denitrification is well known being the most important nitrate-consuming process in water-logged peat soils, whereby the intermediate compound nitrous oxide (N(2)O) and the end product dinitrogen (N(2)) are ultimately released. The present study was aimed at evaluating the release of these gases (due to denitrification) from a nutrient-poor transition bog ecosystem under drained and three differently rewetted conditions at the field scale using a (15)N-tracer approach ([(15)N]nitrate application, 30 kg N ha(-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 93 publications
4
18
0
Order By: Relevance
“…For instance, Rückauf et al (2004) [29] performed 15 N tracer experiments in drained and reflooded microcosms filled with fen peat and found that denitrification was the main N transformation process, whereas N 2 O emission from reflooded (anoxic) conditions was significantly lower than that from drained microcosms. Similar results were gained in field studies by Tauchnitz et al (2015) [30] with 15 N tracer studies on nitrogen gases released from a transition bog and found high N 2 O and low N 2 from drained conditions and the reversed situation in rewetted cases. Likewise, Yang et al (2011) [31] found significantly higher emission from drained soils with oxic conditions, using field-based 15 N-N 2 O pool dilution technique to measure gross N 2 O production in soil.…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…For instance, Rückauf et al (2004) [29] performed 15 N tracer experiments in drained and reflooded microcosms filled with fen peat and found that denitrification was the main N transformation process, whereas N 2 O emission from reflooded (anoxic) conditions was significantly lower than that from drained microcosms. Similar results were gained in field studies by Tauchnitz et al (2015) [30] with 15 N tracer studies on nitrogen gases released from a transition bog and found high N 2 O and low N 2 from drained conditions and the reversed situation in rewetted cases. Likewise, Yang et al (2011) [31] found significantly higher emission from drained soils with oxic conditions, using field-based 15 N-N 2 O pool dilution technique to measure gross N 2 O production in soil.…”
Section: Introductionsupporting
confidence: 82%
“…We also observed temporal variation of emissions from each position. High spatial and temporal variability of fluxes seems to be typical for N2O and has been observed in both mineral and organic soils [7][8][9]27,30,37,38,40]. Characteristically large temporal variations of N2O emissions have also reported in a review paper by Henault et al (2012) [45].…”
Section: N2o Emissions Varying With Water Tablementioning
confidence: 79%
“…The average 15 N tracer application rate (0.04-0.5 kg 15 N ha −1 or 0.4-1.2 mg 15 N kg −1 dry soil) across land use types was 1 to 2 orders of magnitude lower than previous applications of the 15 N gas-flux method in highly fertilized agricultural systems (Baily et al, 2012;Bergsma et al, 2001;Cuhel et al, 2010;Graham et al, 2013) and in restored peatland soils (Tauchnitz et al, 2015). The estimated enrichment of the total soil NO − 3 pool was variable (2-40 15 N at %, Table S2) and this wide range was due to the fact that the tracer concentration was calculated based on the previous campaign's soil nitrate data, which in some cases did not reflect the soil nitrate content on the day of the tracer application a month later.…”
Section: Field Application Of the 15 N Gas-flux Methodsmentioning
confidence: 73%
“…Most studies using 15 N tracers and static chambers in highly fertilized systems typically deploy their chambers between 1 and 2 h (Baily et al, 2012;Cuhel et al, 2010;Tauchnitz et al, 2015), but it has been shown that longer incubation periods (up to 24 or 48 h) may be needed in case of low 15 N enrichment applications in intact soil cores (Morse and Bernhardt, 2013) and laboratory incubations (Yang et al, 2014) for a more precise and accurate detectable 15 N-N 2 signal. However, it should be noted that in these cases the soil cores or slurries were incubated in fully enclosed systems and were thus not affected by potential bias from diffusion of evolved N 2 and N 2 O to the subsoil (Clough et al, 2005).…”
Section: Field Application Of the 15 N Gas-flux Methodsmentioning
confidence: 99%
See 1 more Smart Citation